A STUDY ON THE ANTITUMOUR EFFECT OF TOTAL FLAVONOIDS FROM PTERIS MULTIFIDA POIR IN H22 TUMOUR-BEARING MICE - Yu, Canqiu; Chen, Jinwei; Huang, Li (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to investigate the inhibitory effect of total flavonoids from Pteris multifida Poir on growth of transplanted H22 tumour in mice. H22 tumour-bearing mice model was established; the experimental animals were divide/d into the model group, Pteris multifida Poir total flavonoids high-, low-dose groups, and CTX group. Pteris multifida Poir groups were administered continuously for 10d, and CTX group was administered every other day. Tumour inhibition rate, thymus index and spleen index were calculated. Serum levels of TNF-α and IL-2 were determined, as well as total antioxidant capacity (T-AOC) and malondialdehyde (MDA) levels in serum. Compared with the model group, the total flavonoids of Pteris multifida Poir can significantly inhibit tumour growth, with tumour inhibition rates of high- and low-dose groups 49.36% and 33.97%, respectively. They can also evidently increase the spleen and thymus indices of tumour-bearing mice, elevate serum TNF-α and IL-2 levels increase serum T-AOC level and reduce serum MDA level in tumour-bearing mice. The study concluded that total flavonoids from Pteris multifida Poir has an obvious inhibitory effect on transplanted H22 tumours; its mechanism of action may be associated with the improvement of immune function and enhancement of antioxidant capacity in mice.